APAKAH MANAJEMEN LABA TERMASUK KECURANGAN ? : ANALISIS LITERATUR - Deddy Kurniawansyah (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2018)
Many maintain that earnings management is harmful. This literature study explains and describe the issue from the outside perspective of earnings management. This research  method  used  qualitative  with  literature  study. The  results  of  this  study  are Earnings management is not a fraud. Fraud is an “act of criminal deception” or a “deceitful  behavior  which  may  be  punished  by  law”.  Earnings  management  is within legitimate constraints, implying that the deviation of reported earnings from underlying  or  economic  earnings  due  to  earnings  management  is  legitimate  or authorized by accounting standards  and corporate laws.  The results of this study contribute  as  add  to  the  treasury  of  financial  accounting  literature,  especially accounting  theory.  The  results  of  this  research  have  important  implication  for regulators  and  lawmakers.  Regulators  tend  to  regard  earnings  management  as harmful and in the need of immediate remedial action.